Acting Independently in Decision-Making: Its Correlation with Student Engagement in REI Study Program Lectures - Robi Zulfikar; Nandia Ayuzmal; Nuriski Hairuniska; Ratna Juwita; Nur Fadilah; Sherfina Indah Aprilia; Siti Zulaikhah (Action Research Journal Indonesia (ARJI), 2025)
This study aims to analyze the relationship between decisional autonomy—as an aspect of self-confidence—and student engagement in learning within the Islamic Education program at UIN Raden Intan Lampung. The low levels of student engagement (33 %) and decisional autonomy (34 %) provided the rationale for this investigation. A quantitative ex post facto design was employed with 81 fifth-semester students in the 2024/2025 academic year, selected by simple random sampling from a population of 414. Data were collected via a Likert-scale questionnaire whose validity and reliability had been established. The analysis included tests for normality, homogeneity, linearity, and heteroskedasticity, as well as t-tests, F-tests, and the coefficient of determination, all conducted using IBM SPSS Statistics version 23. The results indicate that decisional autonomy has a positive and significant effect on student engagement, with a significance value of 0.017 (p < 0.05) and an F-statistic of 5.906. However, decisional autonomy accounts for only 7 % of the variance in engagement (R² = 0.070), while the remaining 93 % is attributable to factors beyond the scope of this study. This research contributes novel insights by simultaneously revealing the psychological and pedagogical interplay in an Islamic Education context that has traditionally relied on lecture methods and material perceived as insufficiently aligned with students’ career objectives. The findings may inform instructors in designing more interactive and relevant instructional strategies to enhance both decisional autonomy and student engagement.